Clustering effects on firm exporting with productivity‐enhancing R&D in China. (1st October 2019) - Howell, Anthony
Abstract: This paper examines the effects of regional clustering on the linkages among R&D, exporting and productivity of Chinese firms. A structural framework is employed using a set of recursive equations that is capable of correcting for most estimation issues related to selection and endogeneity. The main findings reveal that regional clustering brings about relatively trivial direct benefits to exporters after taking into account important sources of firm heterogeneity. Rather, the main benefits of clustering on exporting appear to arise indirectly through investments in innovation and productivity. The main implication of the findings suggests that a better endowed geographical area improves international competitiveness mainly by enhancing the super‐additive effects of investments in technology on productivity, which, in turn, enhances exporting performance.